Biodiesel from agricultural residues - Teleki, Bela Istvan (GEORGIKON FOR AGRICULTURE, 2020)
The author of this article has made his library research at Burgenland University of Applied Sciences, Munich University of Applied Sciences, University of Pannonia and Slovak University of Technology. The latter one gave place for the 8-week series of experiment, during which period he produced biodiesel from raw oil and waste cooking oil using different additives. Due to the evaluation of the products it is recognized that due to the costs of catalysts and energy (additionally limited market for side-products) biofuel production is not profitable under today’s economic conditions. However, for farmers growing oil crops on their undervalued arable land, sharing biorefineries could be a potentially refunded enterprise. The number of energy crops successfully applied in Hungary are increasing, partly because the European Union is determined to support the domestication of tropical plants on the continent in order to reduce dependence on foreign oil. With this documentation I’d like to map down some alternative feedstock of the biofuel industry, examining its legal background and chemical procedures, eventually main lines ofcurrent scientific researches.